Annual Plan 2008-09 Volume-II (Sectoral Summary) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2008)
Agriculture, despite its recent lackluster performance and consistent decline in its contribution to the economy, remained mainstay for millions of people in the state. Food security and providing gainful employment to the labour force, especially to those engaged in agriculture sector virtually became a cynosure and continue to attract the attention of the Planners and Policy makersboth at the National level as well as at the state level in the 11th Five Year Plan. The envisaged growth in excess of 4% in the Agriculture sector during the 11th Plan is possible only if the farm incomes improve substantially and the excess labour in this sector find an alternative yet profitable employment opportunities in the non-farm rural sector, that is expected to offer a relatively higher wage.
Planning Department, Government of Andhra Pradesh